2004
DOI: 10.1262/jrd.50.587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Replacement of Pyruvate/Lactate in Culture Medium with Glucose on Preimplantation Development of Porcine Embryos In Vitro

Abstract: Abstract. The effect of glucose supplementation at different times in in vitro culture on the developmental competence of in vitro produced (IVP) porcine embryos was examined. In Experiment 1, when IVP embryos were cultured in modified NCSU-37 supplemented with pyruvate and lactate (IVC-pyr/lac) for 0 h, 24 h, 48 h, 72 h, 96 h, or 118 h and subsequently in modified NCSU-37 supplemented with glucose (IVC-glu) until Day 6 (Day 0=day of in vitro fertilization), the rates of blastocyst formation were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Abnormal cell division was also observed in porcine embryos produced by IVF at the first cleavage division (unpublished our data). The average number of cells per blastocyst found in the present study was similar to that previously reported by Kikuchi et al [8], Somfai et al [33] and Karja et al [34]. Blastocysts derived from 3-to 4-cell embryos and 5-to 8-cell embryos had significantly more cells than those from the other cell stage embryos.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Abnormal cell division was also observed in porcine embryos produced by IVF at the first cleavage division (unpublished our data). The average number of cells per blastocyst found in the present study was similar to that previously reported by Kikuchi et al [8], Somfai et al [33] and Karja et al [34]. Blastocysts derived from 3-to 4-cell embryos and 5-to 8-cell embryos had significantly more cells than those from the other cell stage embryos.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the overall blastocyst rate (23.1%) for all the inseminated oocytes was similar to the rate previously reported by Kikuchi et al [8] (25.3%); however, it was slightly lower than the rates reported by Somfai et al [33] (32%) and Karja et al [34] (31.3%). When the embryos were classified by their cleaved stages on Day 2, the blastocyst rate of the moderate stage embryos (3-to 4-cell and 5-to 8-cell embryos) was significantly higher than the rates of the delayed or slow (2-cell embryos) and fast stage (>8-cell embryos) embryos.…”
Section: Discussionsupporting
confidence: 90%
“…An alternative is to use embryos produced entirely in vitro. Obviously, a critical component in generating in vitro embryos is the culture medium in which they are grown.Several reports have investigated improving two commonly used porcine embryo culture media, North Carolina State University 23 and 37 (NCSU23 and NCSU37;[2]) [3][4][5]. As originally formulated, these media contain only glucose as the primary energy substrate.…”
mentioning
confidence: 99%
“…Karja et al [4] found the optimum time to change modified NCSU37 supplemented with pyruvate and lactate to modified NCSU37 supplemented with glucose was 58 h after the start of culture. However, the optimum time to change the energy substrates and add EAA has not yet been adequately investigated with porcine embryos in our modified NCSU23.…”
mentioning
confidence: 99%
“…Several reports have investigated improving two commonly used porcine embryo culture media, NCSU-23 and 37 (Raychoudhury and Suárez, 1991;Kikuchi et al, 2002;Karja et al, 2004;Beebe et al, 2009). Very few experiments have studied the use of hormones in the maturation of porcine oocytes (Eroglu, 1993;Bing et al, 2001;Dode and Graves, 2002).…”
Section: Discussionmentioning
confidence: 99%